THE COMPOSITION TEST OF TILAPIA FEED (Oreochromis niloticus) WITH ADDITION OF FLOUR E. cottonii FERMENTED USING TAPE YEAST AND EM-4 - Nita Annisah Al Barru; Nita Salnida Dewi; Dewi Putri Lestari (AQUASAINS, 2022)
This study attempts to analyze the growth of tilapia feed with additional flour E. cottonii fermented with a combination of tape yeast and EM4. This study used a Completely Randomized Design (CRD) with 4 treatment and 3 replications which is P1 (control/0% fermented E. cottoni flour), P2 (4% fermented E. cottoni flour), P3 (8% fermented E. cottoni flour), and P4 (12% fermented E. cottoni flour). Fish maintenance done for 50 days. The observed parameters were absolute growth rate, absolute length growth, specific growth rate, feed efficiency, feed convertion ratio, survival rate and water quality. Data were analyzed using Analysis of Variance (ANOVA) within 95% of trust. The result showed that there is no significant different on the growth, feed efficiency, feed convertion ratio, and survival rate but could potentially be an alternative feed raw materials because it is still capable of producing the same results with control feed.